Consumer perspective on the recycling process. Social media analysis of RetuRO - Brindusa Mariana Bejan; Ciprian Marcel Pop (Journal of Ethics in Entrepreneurship and Technology)
Purpose – This study aims to analyze the attitude of consumers toward the recycling process, especially toward the manner of its promotion through social media platforms. Design/methodology/approach – Using social media analysis, the authors analyzed the posts on the RetuRO page on Facebook. The results showed us that the first posts started in January, the recycling program and the guarantee return systems implementation have been active in the stores since November 30. Thus, the posts from each month were analyzed, observing that at the beginning of the program, the posting frequency was higher (8–10 posts/month), whereas in 2024, the frequency registered a slight decrease. Findings – This paper reflects two facets of consumer attitudes: if at the beginning of the recycling program, the feeling expressed was one of delight and satisfaction because customers had the opportunity to get rid of plastic or glass packaging, respectively aluminum cans, thus contributing to protecting the environment, with the development of the program, their opinions changed. The problems generated by the difficulty of recycling, and the technically deficient aspects of the devices led to a paradigm shift and the manifestation of a negative component of consumer attitudes. Originality/value – To the best of the authors’ knowledge, this study is the first carried out in Romania that analyses the influence of the RetuRO platform in the recycling process carried out in our country using social media analysis.